Peran Pendidikan dalam Menghadapi Tantangan Sosial dan Psikologis yang Dihadapi Generasi Milenial Akibat Ketergantungan terhadap Gadget (Studi Kasus Pemberitaan di Media Online) - Ani Fatimah Zahra Saifi; Erni Susilawati; Euis Komala; Mahmud Mahmud; Pepen Supendi (Departement of Mathematics Education, 2024)
Students are a sub-system of education, namely those who take part in educational programs at various levels, from early childhood education to higher education. They are the main focus in the education system. Education aims to shape, guide and prepare them for the future. However, in online media there is news about children who are addicted to gadgets which is very sad. It seems that the goals of national education and the goals of Islamic education will be difficult to achieve if the millennial generation, which in fact is students, is addicted to gadgets. The purpose of writing this article is to analyze the social and psychological challenges faced by the millennial generation due to dependence on gadgets and the role of education in dealing with these problems. This research uses a qualitative approach with a descriptive case study method. The results of the analysis show that dependence on gadgets can provide certain social challenges for the millennial generation which can disrupt the development of human social relationships so that they cannot develop as complete humans and can cause a number of psychological challenges that will hinder developmental tasks at each phase of children/students. In overcoming the two challenges mentioned above, education has a very significant role.